GAGALNYA PEMERINTAH DALAM PENANGANAN KONFLIK SUMBER DAYA ALAM: STUDI KASUS PADA SENGKETA KAWASAN HUTAN REGISTER 45 KABUPATEN MESUJI, PROVINSI LAMPUNG - Hidayat, Taufiq Tri (Journal of Humanity Studies, 2022)
This paper seeks to critically examine the role or social responsibility of the Government of Mesuji Regency, Lampung Province regarding the natural resource conflicts that occur between the people of Talang Batu Village, Mesuji Regency and PT. Silva Inhutani Lampung (SIL). The results of this study indicate that the Mesuji Regency Government as an agency that serves the needs of the surrounding community failed to show its role in dealing with conflicting resources in the Register 45 Forest Area of Talang Batu Village, Mesuji Regency. A society that has an interest in defending and doing everything from negotiations to violent conflict or anarchism. Therefore, the Mesuji Regency Government, in this case as a mediator, is able to become a problem solver but instead ignores the rights of the socio-economic aspects of small communities.